You poor little thing! The role of compassion for wildlife conservation. Issue 2 (4th March 2021) - Greving, Hannah; Kimmerle, Joachim
ABSTRACT: Citizens can engage in wildlife conservation by participating in citizen science (CS) projects about wildlife. Interest in wildlife and science has been found to be one motivation for CS participation. Yet, we suggest that emotional responses, such as compassion for suffering, injured, or distressed wildlife, are relevant motivations that have so far been understudied. Compassion is known to increase behavioral intentions to alleviate suffering and, thus, is likely to have beneficial consequences for wildlife CS projects. Therefore, our two studies investigated the impact of different wildlife photographs on compassion, attitudes toward CS, and intentions to engage in CS. We found that photographs of distressed raccoons and foxes increased compassion, which thereby increased attitudes toward CS projects and some intentions to participate in these projects. Thus, compassion may be a relevant factor for increasing citizens' engagement in wildlife conservation. We discuss the implications of our findings for CS and wildlife conservation.